Materials and Manufacturing Processes - Kumar, Kaushik; Kalita, Hridayjit; Zindani, Divya; Davim, J. Paulo (Materials Forming, Machining and Tribology,, 2019)
This book introduces the materials and traditional processes involved in the manufacturing industry. It discusses the properties and application of different engineering materials as well as the performance of failure tests. The book lists both destructible and non-destructible processes in detail. The design associated with each manufacturing processes, such Casting, Forming, Welding and Machining, are also covered.